PERSONAL BRANDING MAHASISWA UPN “VETERAN” JAWA TIMUR DI INTERSHIP LIFE (InLiFe) PADA PT TELEKOMUNIKASI SELULER SURABAYA - br Milala, Dian Theovani; Widowati, Dyah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: Internship programs serve as a learning platform that prepares students to face the professional workforce. These programs enable students to apply academic theories in real-world practices, enhance technical and interpersonal skills, and bridge the gap between education and the workplace. In this context, personal branding becomes a key element that helps students stand out in a competitive work environment. Personal branding involves managing self-image through values, skills, personality, vision, mission, and professional image.The Internship Life program, conducted by PT Telekomunikasi Seluler Surabaya, provides an opportunity for students not only to learn professional skills but also to develop and strengthen their personal branding. This program is designed to help students build a strong professional image and increase their competitiveness in the job market. Keywords: Internship, Personal Branding, Internship Life, PT Telekomunikasi Seluler Surabaya Abstak..Program magang merupakan wadah pembelajaran yang mempersiapkan mahasiswa untuk menghadapi dunia kerja secara profesional. Program ini memungkinkan mahasiswa menerapkan teori akademis dalam praktik nyata, meningkatkan keterampilan teknis dan interpersonal, serta menjembatani kesenjangan antara pendidikan dan dunia kerja. Dalam konteks ini, personal branding menjadi elemen kunci yang membantu mahasiswa menonjol di lingkungan kerja kompetitif. Personal branding melibatkan pengelolaan citra diri melalui nilai, keterampilan, kepribadian, visi, misi, dan citra profesional. Program Internship Life merupakan program magang oleh PT Telekomunikasi Seluler Surabaya yang memberi kesempatan untuk tidak hanya belajar keterampilan profesional, tetapi juga mengembangkan dan memperkuat personal branding. Kata Kunci : Magang, Personal Branding, Internship Life, PT Telekomunikasi Seluler Surabaya